(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article examines the problems that arise in the process of machine translation of synonyms in Turkish and Uzbek languages. It is known that today there is great interest in the masterpieces of Turkish literature. For this reason, many Turkish works are translated into Uzbek. Of course, experienced translators help us with this. However, those who wish can make transfers using a machine. Of course, this can save time and money, but how worthwhile are translations done this way? We know that our language is a rich and multifaceted language. In our language there are lexical units such as homonyms, antonyms, polysemantic words and synonyms that create these possibilities. So how many of these units, which form the basis of our language, retain their original meaning in machine translations? Are there semantic issues related to context? We examined these problems in this article.